Unraveling The Climate Crisis: Exploring The Multifaceted Impacts and Causes of Global Climate Change - Mir Mohammad Mohi Uddin Rafi (Al-Makki Publisher, 2024)
This paper is basically about climate change. Climate change describes the changes in the nature of climate including temperature, rainfall and other weather events over a long period of time. Now a days climate change is a major problem all over the world. There are so many effects of climate change on the environment. Due to the increase in temperature global warming occurs. Climate change affects the ecosystem, human system, urban system, economic system, social system and many other aspects. Bangladesh is the worst affected country of climate change. Due to climate change global warming is growing rapidly day by day which is no longer a good thing. The world is turning into warming due to this melting of ice, rising sea levels, deforestation, melting of Himalayan glaciers and many more problems related to this. There are many reasons for climate change but carbon emissions and greenhouse gas emissions are one of the major causes of climate change.